Manufacturing method of sliding parts
Patent Information
- Application Number
- JP2021064131
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-04-05
Smart Images

Figure 0007641537000002 
Figure 0007641537000003 
Figure 0007641537000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid lubricant, a sliding part, a method for producing a solid lubricant, and a method for producing a sliding part. [Background technology]
[0002] Patent Document 1 discloses a mold release agent used in a mold casting method. This mold release agent contains oil and a solid lubricant as mold release components. Sericite is shown as an example of the solid lubricant. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 9-108773 Summary of the Invention [Problem to be solved by the invention]
[0004] Sericite (sericite) is a fine phyllosilicate mineral with a hexagonal plate-like layered structure, and is mainly used in cosmetics, but due to its cleavage it is also expected to be used as a solid lubricant. However, the use of sericite as a solid lubricant has not been fully explored because it contains hard particles such as quartz and feldspar that cause abrasive wear, and because it has low oleophilicity and is difficult to disperse in oil.
[0005] The present invention has been made in view of the above-mentioned conventional circumstances, and aims to provide a solid lubricant and a sliding part having good friction characteristics, as well as a method for manufacturing such a solid lubricant and a method for manufacturing the sliding part. [Means for solving the problem]
[0006] The solid lubricant of the first invention is characterized in that it contains sericite particles having graphite particles attached to the surfaces thereof.
[0007] The solid lubricant of the first invention has good friction characteristics when used in an environment where lubricating oil or grease is present on the sliding surface, and can be suitably used in a high temperature environment.
[0008] The sliding component of the second invention is characterized in that a lubricating coating containing the above-mentioned solid lubricant is formed on the sliding surface.
[0009] According to the sliding surface of the sliding component of the second aspect of the invention, it is possible to reduce frictional resistance and to suppress transfer to a counter material sliding on the sliding surface, thereby improving the sliding characteristics of the sliding component.
[0010] A method for producing a solid lubricant according to a third aspect of the present invention is characterized in that a raw material containing sericite and graphite is pulverized to obtain the above-mentioned solid lubricant.
[0011] According to the method for producing a solid lubricant of the third invention, graphite, which is more easily pulverized than sericite, is pulverized, and a solid lubricant having good friction characteristics and heat resistance can be easily produced.
[0012] A manufacturing method of a sliding component according to a fourth aspect of the present invention is characterized in that a metal film is formed on the surface of a base material, and the above-mentioned solid lubricant is press-fitted into the metal film.
[0013] According to the manufacturing method of the sliding component of the fourth aspect of the present invention, the orientation of the solid lubricant can be improved, and the sliding characteristics of the sliding component can be improved.
[0014] Therefore, it is possible to provide a solid lubricant and a sliding part having good friction characteristics, and also to provide a method for producing such a solid lubricant and a method for producing the sliding part. [Brief description of the drawings]
[0015] [Figure 1] 1A is an SEM image of a solid lubricant according to an embodiment, and FIG. 1B is an SEM image of a composite particle according to an embodiment. [Diagram 2] 1A is a perspective view showing a schematic SEM image of a composite particle, and FIG. 1B is a cross-sectional view taken along line II-II of FIG. [Diagram 3] 1A is a schematic plan view of a sliding component, and FIG. 1B is a cross-sectional view taken along line III-III of FIG. [Figure 4] 4A is an enlarged plan view showing a schematic diagram of a sliding component, and FIG. 4B is a cross-sectional view taken along line IV-IV of FIG. [Diagram 5] FIG. 2 is a diagram conceptually showing a gradient composition of a lubricant coating. [Figure 6] 1 is a graph showing evaluation results of friction characteristics of Example 1 and Comparative Examples 1 to 3. [Figure 7] 1 shows optical microscope images and cross-sectional curves of friction surfaces after testing in Example 1 and Comparative Examples 1 to 3. [Figure 8] 1 is a graph showing the evaluation results of friction characteristics of Examples 1 to 4. [Figure 9] 4 shows optical microscope images and cross-sectional curves of the friction surfaces of Examples 2 to 4 after testing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] A preferred embodiment of the present invention will now be described.
[0017] In the method for producing a sliding component of the fourth aspect of the invention, the metal film into which the solid lubricant has been pressed may be heat-treated to form a lubricating coating. This method can improve the adhesion of the lubricating coating and the sliding characteristics of the sliding component.
[0018] The solid lubricant 10, the sliding part 40, the manufacturing method of the solid lubricant 10, and the manufacturing method of the sliding part 40 according to an embodiment will be described in detail below. In this specification, when a numerical range is described using "to" it is intended to include the lower limit and the upper limit unless otherwise specified. For example, the description "10 to 20" is intended to include both the lower limit "10" and the upper limit "20". In other words, "10 to 20" has the same meaning as "10 or more and 20 or less".
[0019] 1. Solid Lubricants 10 The solid lubricant 10 contains sericite particles 20 having graphite particles 30 attached to their surfaces. Hereinafter, the "sericite particles 20 having graphite particles 30 attached to their surfaces" will also be referred to as "composite particles 11."
[0020] FIG. 1(A) is an SEM image of a solid lubricant 10 observed with a scanning electron microscope (SEM), and (B) is an SEM image of a composite particle 11. In the composite particle 11, a graphite particle 30 is mechanically bonded to a sericite particle 20. Such a composite particle 11 can be obtained by dry grinding a mixed powder of a sericite powder and a graphite powder. As shown in FIG. 1 and FIG. 2, in the composite particle 11, the surface of the sericite particle 20 is covered with the graphite particle 30. For convenience of explanation, FIG. 2 and FIG. 3 are drawn typically with the size, shape, and arrangement of the sericite particle 20 and the graphite particle 30 appropriately changed.
[0021] A "solid lubricant" is a substance that is placed between two objects when they are in relative motion in order to reduce friction, prevent seizure, improve the life of the die, etc. The solid lubricant 10 is used as one component of the lubricating coating 41 of the sliding part 40 shown in Figs. 3 and 4.
[0022] 1-1. Sericite particles 20 The sericite particles 20 are pulverized sericite powder, which is a refined product of sericite, a type of mica. The sericite particles 20 have a layered structure and have cleavage properties. The sericite particles 20 are flaky and well oriented, and have excellent lubricity. The sericite particles 20 contribute to improving the lubricity of the composite particles 11. The sericite particles 20 have heat resistance up to about 1200°C.
[0023] The sericite powder preferably has a sericite content of 95.0% by mass or more, more preferably 99.0% by mass or more. In particular, the sericite powder is preferably a high-purity sericite that satisfies the composition of SiO2 45 vol% or more and less than 50 vol%, Al2O3 33 vol% or more and less than 38 vol%, and K2O 8 vol% or more, and that does not recognize peaks other than muscovite in X-ray diffraction. As such sericite powder, Furikusa sericite produced in the Furikusa region of Toei-cho, Kitashitara-gun, Aichi Prefecture is preferably used. Furikusa sericite is sericite formed by hydrothermal alteration in the Otoge ring-shaped complex rock mass in the Furikusa region. It has been confirmed that Furikusa sericite contains 1.0% or less of other minerals such as quartz and feldspar. Currently, all molybdenum disulfide, which is commonly used as a solid lubricant, is imported, whereas the above sericite can be produced domestically, so a stable supply can be expected.
[0024] The first characteristic of Furikusa sericite is the way the crystals are layered. Polytypes of mica resulting from differences in the way the crystals are layered are known as "1M type (monoclinic lattice)", "2M1 type (two-layer monoclinic lattice)", "2M2 type (two-layer monoclinic lattice)", "3T type (three-layer trigonal lattice)", etc. However, Furikusa sericite does not have various polytypes and is almost purely "2M1 type", making it a valuable resource worldwide. Its shape also has a high aspect ratio (longest particle diameter on the XY axis / longest particle diameter on the Z axis = 20 or more), and the average size of each particle (average particle diameter) is about 10 μm. These characteristics give Furikusa sericite a natural, beautiful luster and smooth feel like silk.
[0025] For example, the Furikusa sericite is obtained from the ore as a raw material for the solid lubricant 10 in the following manner. First, the mined ore is selected and slurried with water to break down the ore and disperse it in water. This dispersion process keeps the sericite dispersed in water, but the large, heavy sulfide minerals and other associated minerals precipitate. Using this characteristic, impurities are removed and only pure sericite is collected by "elutriation" to completely remove other minerals. Next, the particle size distribution is adjusted using a wet cyclone classifier, and the Furikusa sericite is obtained after repeated washing, dehydration, drying, and crushing. Such sericite powder is generally used as a cosmetic raw material. Commercially available products include Sericite FSE manufactured by Sanshin Kogyo Co., Ltd.
[0026] 1-2.Graphite particles 30 The graphite particles 30 are pulverized graphite powder. The graphite particles 30 have cleavage properties. The graphite particles 30 are finer than the sericite particles 20. Graphite is a material that is more easily pulverized than sericite, and by mixing and pulverizing sericite powder and graphite powder, it is possible to obtain graphite particles 30 that are finer than the sericite particles 20. The graphite particles 30 have a higher lipophilicity than the sericite particles 20, and contribute to improving the lipophilicity of the composite particles 11. The graphite particles 30 have heat resistance that can withstand up to about 500°C.
[0027] 1-3.Optional ingredients The composite particles may contain optional components in addition to the sericite particles 20 and the graphite particles 30. An example of the optional components is metal particles. An example of such composite particles is sericite particles having graphite particles and metal particles attached to the surface. The metal particles are preferably one or more metal particles selected from the group consisting of tin (Sn), copper (Cu), zinc (Zn), and nickel (Ni). The composite particles have sericite particles, graphite particles, and metal particles mechanically bonded to them. Such composite particles can be obtained by dry grinding a mixture of sericite powder, graphite powder, and the above-mentioned metal powder.
[0028] The optional components can be appropriately selected depending on the performance required for the solid lubricant, the material of the sliding part 40, and the like. For example, the melting point of tin is about 230°C. Composite particles containing tin particles as metal particles are expected to have the effect of improving the bonding strength of the solid lubricant by heat treatment. As shown in FIG. 4, when the composite particles are used as a lubricating coating 41 combined with a metal film 42, the composite particles preferably contain bronze particles. When the composite particles contain bronze particles, the transfer of the lubricating coating 41 and the wear of the sliding surface 40A can be further suppressed. This is presumably because an alloy structure of Cu, Sn, and a metal film component (e.g., Zn) is formed around the composite particles by heat treatment.
[0029] 1-4. Blend ratio of 20% sericite particles and 30% graphite particles The blend ratio of the sericite particles 20 and the graphite particles 30 can be appropriately set within a range in which the sericite particles 20 can be covered with the graphite particles 30. The blend ratio of the sericite particles 20 and the graphite particles 30 (sericite particles / graphite particles) in parts by mass is, for example, 90 / 10 to 10 / 90, and preferably 90 / 10 to 50 / 50. When the composite particle 11 contains an optional component, the blending amount of the optional component can be appropriately set within a range that does not impair the object of the present invention.
[0030] 1-5. Size of composite particle 11 Composite particle 11 is a generally plate-like particle. Fig. 2 is a schematic diagram of an SEM image of composite particle 11, showing the thickness T of composite particle 11 and the maximum diameter D in a direction perpendicular to the thickness direction. The thickness direction of this composite particle 11 coincides with the c-axis direction of the crystal structure of sericite. There is no particular limitation on the maximum diameter D of the composite particles 11. From the viewpoint of maintaining the crystal structure of sericite and dispersibility of the composite particles 11, the average value of the maximum diameter D of the composite particles 11 is preferably, for example, 1 μm or more and 20 μm or less. The average value of the maximum diameter D of the composite particles 11 can be calculated by measuring the maximum diameter D of 10 composite particles 11 with a scanning electron microscope and averaging the measured values. The average value of the maximum diameter D of the composite particles 11 can be appropriately adjusted by changing, for example, the average particle size of the raw material sericite powder or the grinding conditions when producing the composite particles 11.
[0031] 2. Manufacturing method of solid lubricant 10 The method for producing the solid lubricant 10 includes a step of pulverizing a raw material containing sericite and graphite. In detail, the method for producing the solid lubricant 10 includes a dry pulverization step of dry pulverizing a mixed powder containing sericite powder and graphite powder using a planetary ball mill, and a wet pulverization step of wet pulverizing the pulverized product obtained in the dry pulverization step using a planetary ball mill. The dry pulverization step allows the graphite particles 30 to be suitably bonded to the sericite particles 20. The wet pulverization step allows the composite particles 11 to be finely divided.
[0032] 3. Sliding parts 40 As shown in Fig. 3 and Fig. 4, the sliding component 40 has a lubricating coating 41 containing a solid lubricant 10 formed on a sliding surface 40A. The sliding component 40 is a component that slides in a lubricating environment of, for example, lubricating oil or grease. The sliding component 40 is used in, for example, industrial machinery, aircraft, vehicles, and other machines. The sliding surface 40A has wear resistance, low friction characteristics, and seizure resistance.
[0033] This sliding component 40 includes a substrate 43 and a lubricating coating 41 that covers the surface of the substrate 43. There are no particular limitations on the material of the substrate 43. The material of the substrate 43 is preferably a metal material such as a copper (Cu) alloy.
[0034] The lubricating coating 41 has a composite structure in which the solid lubricant 10 is dispersed in the metal film 42. The constituent material and composition of the metal film 42 are not particularly limited. The metal film 42 may be a metal material selected from the group consisting of copper (Cu), zinc (Zn), tin (Sn), silver (Ag), and alloys thereof, or a metal sulfide such as SnS (tin sulfide). The lubricating coating 41 preferably has a gradient composition region 41A as shown in FIG. 5 at the interface with the substrate 43. The gradient composition region 41A is a region in which the components of the metal film 42 and the substrate 43 are mutually diffused, and the composition gradually changes in the direction perpendicular to the interface. This structure can improve the adhesion of the lubricating coating 41.
[0035] The metal film 42 may have a single-layer structure or a multi-layer structure. As shown in FIG. 3(B), when the metal film 42 has a multi-layer structure in which a first layer 42A and a second layer 42B are laminated in this order on a substrate 43, it is preferable that the metal film 42 has a gradient composition region from the substrate 43 to the second layer 42B. In this case, the first layer 42A is preferably a metal film having a lower melting point than the second layer 42B. A zinc (Zn) film is suitable as the first layer 42A. When the metal film 42 has a multi-layer structure, the material of the second layer 42B can be appropriately selected according to the mating material, the usage environment, etc., while the first layer 42A ensures adhesion to the substrate 43.
[0036] There is no particular limitation on the thickness of the metal film 42. From the viewpoint of improving the bonding strength of the solid lubricant 10, the thickness of the metal film 42 is preferably greater than the thickness T of the solid lubricant 10. From the viewpoint of suppressing softening of the lubricating coating 41, the thickness of the metal film 42 is preferably 10 μm or less.
[0037] The composite particles 11 are oriented, for example, so that the thickness direction (c-axis direction) is approximately perpendicular to the sliding surface 40A, that is, so that the flat surfaces of the sericite particles 20 are approximately parallel to the sliding surface 40A. Note that the orientation of the composite particles 11 means that a higher proportion of the composite particles 11 are oriented in a predetermined direction compared to a configuration in which the composite particles 11 are dispersed in a non-oriented (isotropic) manner. With this configuration, when the sliding surface 40A is rubbed, slippage is likely to occur between the crystal layers of the sericite particles 20, and the friction coefficient can be reduced.
[0038] 4. Manufacturing method of sliding element 40 The manufacturing method of the sliding part 40 includes a film-forming process of forming a metal film 42 on the surface of a substrate 43, a pressing process of pressing a solid lubricant 10 into the metal film 42, and a heat treatment process of heat-treating the metal film 42 with the solid lubricant 10 pressed into it to form a lubricating coating 41.
[0039] 4-1. Film formation process In the film formation process, it is possible to use common film formation methods such as shot blasting, shot peening, wet plating, electroplating, physical vapor deposition (vacuum deposition, sputtering, ion plating, etc.), and chemical vapor deposition. Among these, it is preferable to use a film formation method using projection such as shot blasting and shot peening. When a film formation method using projection is used, an uneven shape is imparted to the surface of the metal film 42, and the solid lubricant 10 can be suitably pressed in. In the film formation process, from the viewpoint of achieving a gradient composition of the lubricating coating 41, a multilayer film of different metal materials may be formed.
[0040] 4-2. Press-in process In the pressing step, the solid lubricant 10 is applied to the surface of the metal film 42, and the solid lubricant 10 is pressed into the metal film 42 by a method such as roller burnishing. According to this configuration, the composite particles 11 can be oriented such that the flat surfaces of the sericite particles 20 are approximately parallel to the surface of the metal film 42 by the pressure during pressing.
[0041] 4-3.Heat treatment process In the heat treatment step, the metal film 42 into which the solid lubricant 10 has been pressed is held at a predetermined temperature for a predetermined time. The predetermined temperature can be set appropriately depending on the metal type of the metal film 42. The predetermined time can be set to 0.5 to 5 hours depending on the metal type of the metal film 42 and the size of the sliding component 40. The heat treatment conditions are preferably those that cause an interdiffusion reaction between the constituent material of the substrate 43 and the constituent material of the metal film 42. By carrying out such heat treatment, the gradient composition region 41A can be suitably formed at the interface between the lubricating coating 41 and the substrate 43. Furthermore, in the metal film 42 having a multilayer structure, the heat treatment conditions may be those that cause an interdiffusion reaction between the layers.
[0042] 5. Other embodiments In addition to the above-mentioned embodiment, the solid lubricant can be used for various applications. The solid lubricant may be used as a release agent interposed between the forging material and the die in order to reduce friction between the forging material and the die. The solid lubricant has a higher heat resistance than release agents such as Teflon (registered trademark), and can be used suitably in high-temperature environments.
[0043] The manufacturing method of the solid lubricant and the manufacturing method of the sliding part are not limited to the method of this embodiment. As long as the graphite particles are attached to the surface of the sericite particles, the joining mode of the sericite particles and the graphite particles is not limited. When a resin film is used for the lubricating coating, the lubricating coating may be formed by applying a resin material in which a solid lubricant is dispersed to the substrate. The heat treatment step is an optional step, and may not be performed depending on the material, application, etc. of the sliding part. The heat treatment conditions may be heat treatment conditions that do not cause an interdiffusion reaction between the constituent material of the substrate and the constituent material of the metal film. EXAMPLES
[0044] The present invention will now be described more specifically with reference to examples and comparative examples.
[0045] 1. Preparation of solid lubricants of examples and comparative examples (1) Example 1 (Sericite + Graphite) A mixed powder was prepared by blending sericite powder with an average particle size of 5 μm and graphite powder according to the composition shown in Table 1. This mixed powder was dry ground for 2 hours using a planetary ball mill, and then wet ground for 8 hours to obtain the solid lubricant of Example 1. In other words, the solid lubricant of Example 1 contains composite particles consisting of only sericite particles and graphite particles. (2) Comparative example 1 (Sericite) A solid lubricant of Comparative Example 1 was obtained in the same manner as in Example 1, except that graphite powder having an average particle size of 5 μm was used instead of the mixed powder. (3) Comparative example 2 (Graphite) A solid lubricant of Comparative Example 2 was obtained in the same manner as in Example 1, except that graphite powder having an average particle size of 5 μm was used instead of the mixed powder. (4) Comparative Example 3 (MoS2) A solid lubricant of Comparative Example 3 was obtained in the same manner as in Example 1, except that molybdenum disulfide powder having an average particle size of 5 μm was used instead of the mixed powder. (5) Example 2 (Sericite + Graphite + Sn) A mixed powder was prepared by blending sericite powder with an average particle size of 5 μm, graphite powder, and tin powder in the composition shown in Table 1. The rest of the process was the same as in Example 1 to obtain a solid lubricant of Example 2. That is, the solid lubricant of Example 2 contains composite particles consisting of only sericite particles, graphite particles, and tin particles. (6) Example 3 (Sericite + Graphite + Zn) A mixed powder was prepared by blending sericite powder having an average particle size of 5 μm, graphite powder, and zinc powder in the composition shown in Table 1. The rest of the process was the same as in Example 1 to obtain a solid lubricant of Example 3. That is, the solid lubricant of Example 3 contains composite particles consisting of only sericite particles, graphite particles, and zinc particles. (7) Example 4 (Sericite+Graphite+Cu+Sn) A mixed powder was prepared by blending sericite powder with an average particle size of 5 μm, graphite powder, copper powder, and tin powder in the composition shown in Table 1. The rest of the process was the same as in Example 1 to obtain a solid lubricant of Example 4. That is, the solid lubricant of Example 4 contains composite particles consisting of only sericite particles, graphite particles, copper particles, and tin particles.
[0046] [Table 1]
[0047] 2. Preparation of sliding parts of examples and comparative examples Brass (C3604) containing 40% Zn was used as the substrate for the sliding parts. A disk-shaped substrate with an outer diameter of 44 mm, an inner diameter of 20 mm, and a thickness of 7.5 mm was produced by turning, and one end surface of the substrate was mirror-finished with a lapping machine. Then, zinc powder with an average particle size of 180 μm was projected on one end surface of the substrate at about 0.6 MPa using a process similar to shot peening to form a Zn film with a thickness of about 1 μm. Tin powder with an average particle size of 70 μm was projected on the Zn film using a similar process to form a Sn film with a thickness of about 2 μm. The solid lubricant of the examples and comparative examples suspended in an organic solvent was applied to the formed film surface, and pressed in by roller burnishing. Then, heat treatment was performed at 240° C. for 3 hours under atmospheric conditions, and test pieces of the sliding parts of the examples and comparative examples on which a lubricating film was formed were obtained.
[0048] 3. Friction characteristic evaluation test The friction characteristics of each test piece were evaluated. The friction characteristics were evaluated using a three-ball-on-disk type device with three spheres as mating materials. The spheres used were chrome bearing steel SUJ2 spheres with a diameter of 6.25 mm, polished so that the contact surface with each test piece was a flat surface with a diameter of 2.5 mm. The three spheres were fixed at equal intervals on a pitch circumference with a diameter of 33 mm. The test conditions were a load of 300 N, a test speed of 0.5 m / s, and a test distance of 1000 m. Automotive engine oil (viscosity index 0W-8) was used as the lubricant. The test was performed in an environment with a room temperature of 22°C to 25°C and a relative humidity of 40% to 60%.
[0049] 4. Evaluation Results (1) Example 1 and Comparative Examples 1 to 3 Fig. 6 is a graph showing the evaluation results of the friction characteristics of Example 1 and Comparative Examples 1 to 3. In the graph of Fig. 6, the vertical axis represents the friction coefficient, and the horizontal axis represents the sliding distance (m). The friction coefficient of Example 1 (Sericite+Graphite, square marks) decreased from 0.05 to 0.02 over a sliding distance of 100 m from the beginning of the experiment, and continued to decrease thereafter, reaching approximately 0.01 by the end of the experiment. The friction coefficient of Comparative Example 1 (Sericite, circle) was about 0.05 at the beginning of the experiment, decreased as the sliding distance increased, and reached about 0.02 at the end of the experiment. The friction coefficient of Comparative Example 2 (Graphite, diamond mark) was high at about 0.07 from the beginning of the experiment, and increased as the sliding distance increased, reaching about 0.09 at the end of the experiment. The friction coefficient of Comparative Example 3 (MoS2, triangle mark) was about 0.06 at the beginning of the experiment and decreased as the sliding distance increased. The friction coefficient of Comparative Example 3 was about 0.03, lower than that of Comparative Example 1, at a sliding distance of 200 m, but became 0.02 at the end of the experiment, which was about the same as that of Comparative Example 1.
[0050] 7 shows optical microscope images and cross-sectional curves of the friction surfaces after testing in Example 1 and Comparative Examples 1 to 3. The upper row shows the optical microscope image and cross-sectional curve of the counterpart material (sphere), and the lower row shows the optical microscope image and cross-sectional curve of the test piece (disc). The scale of the cross-sectional curves is indicated by arrows on the left side. In Comparative Example 2 (Graphite), discoloration was observed on the counter material (sphere) and wear to a depth of about 1 μm was observed on the test piece (disk). From this, it is believed that in Comparative Example 2, the lubricating coating on the test piece side was transferred to the counter material side. On the other hand, Example 1 (Sericite + Graphite) caused less discoloration of the counterpart material (sphere) than Comparative Example 2 (Graphite) and Comparative Example 3 (MoS2). Example 1 suppressed the transfer of the lubricating coating of the test piece (disk) more than Comparative Examples 2 and 3.
[0051] (2) Examples 1 to 4 Fig. 8 is a graph showing the evaluation results of the friction characteristics of Examples 1 to 4. In the graph of Fig. 8, the vertical axis represents the friction coefficient, and the horizontal axis represents the sliding distance (m). The coefficient of friction for Example 1 (Sericite+Graphite, square marks) is as described above. The friction coefficient of Example 2 (Sericite+Graphite+Sn, triangle mark) was high at about 0.09 at a sliding distance of 100 m, and decreased to about 0.07 at a sliding distance of 400 m, but was still higher than Examples 1, 3, and 4 at the end of the experiment. The friction coefficient of Example 3 (Sericite+Graphite+Zn, diamond mark) was about 0.03 at a sliding distance of 100 m, but increased as the sliding distance increased, reaching about 0.04 at the end of the experiment, which was higher than that of Example 1. The friction coefficient of Example 4 (Sericite+Graphite+Cu+Sn, circle) rapidly decreased from about 0.05 at the beginning of the experiment to about 0.01 at a sliding distance of 100 m, and then maintained a low value of about 0.01 until the end of the experiment.
[0052] 9 shows optical microscope images and cross-sectional curves of the friction surfaces after testing in Examples 2 to 4. The upper row shows the optical microscope images and cross-sectional curves of the counterpart material (sphere), and the lower row shows the optical microscope images and cross-sectional curves of the test piece (disc). The scale of the cross-sectional curves is indicated by arrows on the left side. In Example 2 (Sericite+Graphite+Sn), discoloration was observed in the mating material (sphere) and wear was observed in the test piece (disc). In Example 3 (Sericite+Graphite+Zn), part of the mating material (sphere) was discolored, and although the test piece (disk) did not show wear to a depth of 1 μm or more, discoloration was observed on the sliding surface. In Example 4 (Sericite+Graphite+Cu+Sn), the cross-sectional curve of the mating material (sphere) showed less variation compared to Examples 1 to 3, and the test piece (disk) showed no wear to a depth of 1 μm or more. From this, it is believed that the transfer of the lubricating coating and wear of the sliding surface were suppressed in Example 4.
[0053] 5. Effects of the embodiment As a result of evaluating the friction characteristics of Example 1 (Sericite+Graphite), it was found that transfer to the counter material was suppressed and the friction coefficient was reduced. Moreover, Example 4 (Sericite+Graphite+Cu+Sn) had a further reduced friction coefficient than Example 1. It was suggested that Examples 1 and 4 can be used as solid lubricants with a lower friction coefficient than molybdenum disulfide. Furthermore, the results of Examples 2 to 4 suggested that the friction characteristics can be appropriately designed by changing the metal type of the optional components.
[0054] The present invention is not limited to the above-described embodiments, and various modifications and variations are possible within the scope of the claims of the present disclosure. [Explanation of symbols]
[0055] Reference Signs List 10: solid lubricant, 11: composite particles, 20: sericite particles, 30: graphite particles, 40: sliding parts, 40A: sliding surfaces, 41: lubricating coating, 41A: gradient composition region, 42: metal film, 42A: first layer, 42B: second layer, 43: substrate
Claims
1. A method of producing a solid lubricant comprising the steps of: pulverizing a raw material containing sericite and graphite to obtain a solid lubricant containing sericite particles having graphite particles attached to the surface thereof; A metal film is formed on the surface of the substrate, A method for manufacturing a sliding part, comprising press-injecting the solid lubricant into the metal film.
2. 2. The method for producing a sliding part according to claim 1, wherein a lubricating coating containing said solid lubricant is formed on the sliding surface.
3. 2. The method for producing a sliding part according to claim 1, wherein the metal film into which the solid lubricant has been pressed is heat-treated to form a lubricating coating.
Citation Information
Patent Citations
Aluminum type composite sliding material and its production
JP1993202441A
Self-lubricating composite material and preparation thereof
JP1996283759A
Lubricating coating agent for hot forging
JP1996311468A
Release agent for die casting
JP1997108773A
Sliding member and its manufacturing method
JP2001141183A